Cash flow-investment relationship in Malaysia: a panel threshold regression analysis - Mohd Adib Ismail; Mawar Murni Yunus (Penerbit Universiti Kebangsaan Malaysia, 2015)
The objective of this article is to analyse the relationship pattern of cash flow-investment among low and high debt firms. To investigate the issue, we employed Hansen’s (1999) threshold method of non-dynamic panel data. In this article, the firm debt ratio was used as threshold variable. A balanced panel data of companies listed on Bursa Malaysia, comprising of 234 companies for a period from 2004 to 2010, was utilized in this study. The results showed that debt ratio has a significant role at explaining the cash flow-investment relationship among firms. In particular, the results showed that low debt firms exhibit significant support to the financial constraints hypothesis, while high debt firms demonstrate support to the free-cash flow hypothesis. This finding explains why the cash flow-investment relationship of certain firms is negative, while other firms are positive. It also signifies the inability of constrained firms to access to external financing; thus, leading the firms to significantly rely on their internal financings.